Enhancement of thermoelectric properties for doped skutterudites based on CoSb3 through ball milling parametric optimization / Md Ovik Raihan - Md Ovik, Raihan (2018)
In search for green energy harvesting materials, thermoelectric technology has been identified as a promising technology to generate electricity from waste heat through the presence of a temperature gradient. Skutterudite a viable candidate for high performance thermoelectric material given its advantages of modifying its structure such as doping, filling, substitution in its cage structure to achieve high performance; making its one of the sophisticated member of the thermoelectric application. In this work a new composition of Bi doped and Fe substituted Co3Sb12 system was successfully synthesized by two step process namely ball milling and spark plasma sintering. The ball milling process produce nanostructures. Which are expected to give superior TE properties through reduction in thermal conductivity. Three different ball milling time were investigated: 10h, 15h, 20 h and their correlation to the thermoelectric properties studied in this thesis. Introduction of the Co and Bi with heat treatment resulted in a successful formation of Bi-0.6FeCo3Sb12 skutterudite. Which is expected to give better thermoelectric performance through substitution of Co with Fe and the Bi doping. The phase structure and morphology of the bulk samples were examined by X-ray diffraction (XRD) and scanning electron microscopy integrated energy-dispersive X-ray spectroscopy analysis (SEM-EDS), respectively. . Rietveld analysis of its XRD spectra indicated that the Bi doping on the Co4Sb12 based skutterudite succeeded in partially filling the voids of the skutterudite, whilst the Fe doping partially substituted the Co sites in the lattice. The thermoelectric properties of the Bi filled and Fe substituted bulk samples were measured in a temperature range of 373 K to 673 K. Evidently all of the Bi doped and Fe substituted samples showed a dominant phase of CoSb3 skutterudite. Comparative study among the Bi filled, Fe substituted samples were done. The ball milling times was correlated to the resulting microstructure, and ultimately, its thermoelectric performance. It was found that the moderate ball milling times (at 15 hours) resulted in the best electrical conductivity of 122K Ω-1m-1 at 373 K, given the homogenous distribution of particles. A Maximum ZT value was observed 0.17 for 10 h ball milled sample at 673 K, whilst almost the same value was achieved for the 15 h ball milled sample , i.e ZT =0.169 at 673 K. This work provides a pathway for improvement of the electrical conductivity and decreasing the thermal conductivity, and is thus a useful strategy for future design of skutterudite materials for thermoelectrics. The analysis of the effect of the ball milling conditions on the thermoelectric performance of this formulations also gives insight to the optimal conditions which may yield a good microstructure, and hence good thermoelectric performance. It has been shown that moderate milling times will provide a well distributed sample which is conducive for good electrical conductivity and low thermal conductivity. This work also demonstrated that milling time is able to affect the final composition of the skutterudite in terms of the amount of Bi filling, despite using the same nominal composition for all three samples.